A pedagogia terapêutica de João dos Santos e as contribuições de Maria Amália Borges de Medeiros - caminhos de luta, afeto e conquistas - Borges, Karine Moura de Farias (2022)
This thesis aimed to understand the theoretical and methodological bases that permeated the ideas of João dos Santos, Portuguese physician, psychoanalyst, and educator, as well as the circulation of his ideas in different contexts and temporalities. His theory has a solid base in Psychoanalysis and influences from Genetic Psychology, as well as from Psychopedagogy, whose convergence represents more than a theoretical postulate as it feeds on an ethical and humanistic understanding of the human being. It started from the following question-problem: what is the legacy built by João dos Santos and the contributions of Maria Amália Borges for the theoretical and methodological innovation of the teaching and learning processes and, consequently, of the pedagogical practices? It was based on the methodological assumptions of Oral History, through interviews conducted in a relational context between researcher and interviewees, followed by the literal transcription of the contents of each of the interviews conducted with educators, collaborators and important agents for the dissemination and deepening of João dos Santos' work. The empirical research sought to gather contents about João dos Santos' experiences in Portugal and France, especially in the city of Paris, as well as to make an inventory of the extension of his legacy in the city of Montreal, Canada, in the person of Maria Amália Borges. In Portugal, specifically in the city of Lisbon, we used the methodology of semi-structured interviews with João dos Santos' family members, specialists, and collaborators, where we could get to know the places where João dos Santos worked and traveled, especially in the institutions he founded, such as the Pestalozzi Kindergarten, in 1955, and the Eduardo Claparède School, in 1954. The study starts, especially, from the following authors: João dos Santos (1982, 1991, 2013, 2014, 2016, 2017), Maria Eugênia Carvalho e Branco (2013, 2010), Paula Santos Lobo (1994, 2016), Manuela Cruz (1994, 2016), Patrícia Holanda (2016, 2017, 2018, 2019), Maria Isabel Vieira Pereira (1989, 2013, 2014), Maria Amália Borges de Medeiros (1970, 1975, 1977). The study reveals that Therapeutic Pedagogy brought immense innovations to the education of children and that the partnership between Maria Amália Borges and João dos Santos, based on modern conceptions of the child, of the world, and of education, left a legacy that makes us able to still dream of an education that focuses on the formation of the subject in a caring and affective way.